Prospective Multicenter Open-Label One-Arm Trial Investigating a Pumpkin Seed, Isoflavonoids, and Cranberry Mix in Lower Urinary Tract Symptoms/Benign Prostatic Hyperplasia: A Pilot Study - Elie Nemr; Elie El Helou; Georges Mjaess; Albert Semaan; Josselin Abi Chebel (Advances in Urology)
Phytotherapy for lower urinary tract symptoms (LUTSs) due to benign prostate hyperplasia (BPH) is progressively demanded by patients and trusted by physicians. The aim was to assess the efficacy of a mix of pumpkin seed extract, soy germ isoflavonoids, and cranberry (Novex®) in the management of mild to moderate LUTS in BPH patients. Male patients aged ≥40 years, who had had mild to moderate LUTS for >6 months at screening, with no previous therapy or who are still symptomatic despite current use of alpha-blockers, were recruited. Exclusion criteria were an IPSS >19 and an age >80 years. The mixed compound was administered orally, daily, for 3 months. Patients were evaluated by means of IPSS, urological quality of life (uQoL) index, and International Index of Erectile Function (IIEF-5) at 3 visits: baseline (visit 1), 30 days (visit 2), and 90 days after treatment (visit 3). Among 163 screened patients, 128 patients (61.8 ± 9.9 years) were recruited. IPSS improved from 15 (Q1 : 12–Q3 : 17) in visit 1, to 11 (Q1 : 8–Q3 : 14) in visit 2, and to 9 (Q1 : 6–Q3 : 12) in visit 3 (p<0.001). uQoL improved from 4 (3–4) in visit 1, to 3 (2–3) in visit 2, and to 2 (1–2) in visit 3 (p<0.001). The patients had an IIEF-5 score of 15 (12–18.7) in visit 1, 15 (12–18) in visit 2, and 17 (13–19) in visit 3 (p=0.99 visits 1 vs. 2, p=0.004 visits 2 vs. 3, and p=0.001 visits 1 vs. 3). Treating mild to moderate LUTS/BPH patients with Novex® might therefore relieve symptoms, improve the quality of life, and have a mild beneficial effect on erectile function.